Aflatoxin M1 levels in urine and breast milk of lactating mothers in Kuala Lumpur, Malaysia - Aminuddin, Alyaa Izzati; Jamaluddin, Rosita; Mohd Shukri, Nurul Husna; Sabran, Mohd Redzwan (Taylor and Francis, 2024)
Aflatoxins are carcinogens that can contaminate food and affect various body organs especially liver and kidney. When consumed, aflatoxin B1 (AFB1) is partially metabolised into aflatoxin M1 (AFM1), which is excreted in the urine.Breast milk may also contain AFM1 due to maternal dietary intake from contaminated food. This cross-sectional study aimed to determine the levels of AFM1 in both urine and breast milk among breastfeeding mothers (n = 256). The mother’s demographic information was collected during recruitment. Mothers were then scheduled for an appointment to provide a morning urine sample along with five to ten ml samples of breast milk. AFM1 levels in both samples were analysed using an enzyme-linked immunosorbent assay (ELISA). Spearman’s rho and Chi-square were used to determine the associations between mean levels of AFM1 in urine and breast milk. Findings show 68.0% of urine samples were contaminated with AFM1 (mean levels = 0.08 ± 0.04 ng/mL), while 14.8% of breast milk samples had AFM1 (mean levels = 5.94 ± 1.81 ng/kg). Urine AFM1 levels were not significantly associated with AFM1 levels in breast milk (p > 0.05). This study can act as a baseline for future research examining long-term aflatoxin exposure among both mothers and infants